UTILIZATION OF MOLE (LOCAL MICROORGANISM) OF MAS CONCH AND AGE OF SEED ON RICE GROWTH AND PRODUCTION - Zainal Abidin Zainal; Moch. Bintaro; Suwardi Suwardi; Rusmini; La Mudi; Nur Hidayat; Yuanita Yuanita; Riama Rita Manullang; Roby Roby; Daryono; F. Silvi Dwi Mentari; Faradilla Faradilla (Politeknik Pertanian Negeri Samarinda, 2022)
Rice (Oryza sativa L.) is a food crop as an energy source that is generally consumed by the Indonesian people so that demand continues to increase every year. One of the efforts to increase rice production can be done through the use of young seedlings and microbes to accelerate the process of soil fertilization. This microbe is obtained from the Mas Conch Pest which is processed into Local Microorganisms (MOL). This study aims to determine the effect of giving MOL golden snail and seedling age on the growth and production of rice. This study used a Randomized Block Design (RAK) consisting of 9 treatment combinations and 3 replications. The first factor is the MOL concentration of golden snail, consisting of: 0 ml/L concentration or control, 20 ml/L concentration, and 40 ml/L concentration. The second factor is the age of the seedlings, consisting of: 17 days after sowing), 11 days after sowing and 15 days after sowing. The results showed that the treatment with a concentration of 40 ml/l of Local Microorganisms Conch Mas (M) had a significant effect on the number of productive tillers, the number of pithy grain per panicle and production per hectare. While the age of 7 days after seedling had a significant effect on the number of pithy grain per panicle, weight of 100 grains, and production per hectare. The interaction between the MOL concentration of 20 ml/l golden snail and 7 days after sowing (M1U1) gave a significant effect on the weight of 100 grains.